Sustainability of using the WHO surgical safety checklist: a mixed-methods longitudinal evaluation following a nationwide blended educational implementation strategy in Madagascar. Issue 6 (20th December 2018) - White, Michelle C; Randall, Kirsten; Ravelojaona, Vaonandianina A; Andriamanjato, Hery H; Andean, Vanessa; Callahan, James; Shrime, Mark G; Russ, Stephanie; Leather, Andrew J M; Sevdalis, Nick
Abstract : Background: The WHO Surgical Safety Checklist reduces postoperative complications by up to 50% with the biggest gains in low-income and middle-income countries (LMICs). However in LMICs, checklist use is sporadic and widespread implementation has hitherto been unsuccessful. In 2015/2016, we partnered with the Madagascar Ministry of Health to undertake nationwide implementation of the checklist. We report a longitudinal evaluation of checklist use at 12–18 months postimplementation. Methods: Hospitals were identified from the original cohort using purposive sampling. Using a concurrent triangulation mixed-methods design, the primary outcome was self-reported checklist use. Secondary outcomes included use of basic safety processes, assessment of team behaviour, predictors of checklist use, impact on individuals and organisational culture and identification of barriers. Data were collected during 1-day hospital visits using validated questionnaires, WHO Behaviourally Adjusted Rating Scale (WHOBARS) assessment tool and focus groups and analysed using descriptive statistics, multivariate linear regression and thematic analysis. Results: 175 individuals from 14 hospitals participated. 74% reported sustained checklist use after 15 months. Mean WHOBARS scores were high, indicating good team engagement. Sustained checklist use was associated with an improved overall understanding of patient safety but not with WHOBARS, hospital size or surgical volume. 87% reported improved understanding of patient safety and 83% increased job satisfaction. Thematic analysis identified improvements in hospital culture (teamwork and communication, preparation and organisation, trust and confidence) and hospital practice (pulse oximetry, timing of antibiotic prophylaxis, introduction of a surgical count). Lack of time in an emergency and obstructive leadership were the greatest implementation barriers. Conclusion: 74% of participants reported sustained checklist use 12–18 months following nationwide implementation in Madagascar, with associated improvements in job satisfaction, culture and compliance with safety procedures. Further work is required to examine this implementation model in other countries.